Uso de fones de ouvido por trabalhadores do mercado financeiro - Hidaka, Mariene Terumi Umeoka (2021)
Introduction: Some professions have headset as a mandatory work accessory, for example telemarketing services workers. For employees of Financial Institutions, the usage of headsets serves as a strategy to concentrate, focus attention and reduce background noise as they work in open plan offices. Objective: To investigate the implications of headsets usage by employees working within Financial Institutions in open-plan offices. Method: Retrospective and descriptive study of Financial Institutions employees’ medical records. Data related to sociodemographic profile, pure tone audiometry, health conditions, hearing complaints and usage of headsets were collected, inputted into an excel spreadsheet and submitted for descriptive analysis. Results: 1943 medical records were analyzed, with an age range between 18 and 60 years old, 65.62% male and 34.37% female. 96.6% with hearing thresholds were found to be within the normal range and 3.4% with hearing loss. From the 74.9% headset users, 4.2% reported tinnitus. The analysis of the association between the presence of the audiometric notch and age group was statistically significant (p <0.001) and predominantly at the left ear (9.1%). Conclusion: Whilst is not possible to associate the usage of headsets with identified hearing loss, it is essential to note that 9.1% of this group had an audiometric notch, which emphasizes the need for further research with a larger sample size and in addition education regarding hearing health.in hearing health education